English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

The formula for the distance is:
sqrt((x2-x1)^2+(y2-y1)^2)
sqrt((5-(-3))^2+(3-0)^2)
sqrt(8^2+3^2)
sqrt(64+9)
sqrt(73)
~ 8.544

2007-01-26 12:22:36 · answer #1 · answered by Mark P 5 · 0 1

(5,3) and (-3,0)

D = sqrt((-3 - 5)^2 + (0 - 3)^2)
D = sqrt((-3 + (-5))^2 + (-3)^2)
D = sqrt((-8)^2 + 9)
D = sqrt(64 + 9)
D = sqrt(73)

ANS : about 8.544

2007-01-26 22:42:50 · answer #2 · answered by Sherman81 6 · 0 0

You want us to do your homework for you? How are you ever going to learn it that way?

2007-01-26 20:26:55 · answer #3 · answered by kiwi 7 · 0 0

fedest.com, questions and answers